Enhancement of stress response in Chinese cabbage through eugenol and clove essential oil - Li-Ching Hsieh; Zhi Thong Soh; Wei-An Tsai; Ting-Fang Chen; Hsin-Hung Lin; Jeng-Shane Lin (Current Plant Biology, 2024)
Chinese cabbage (Brassica rapa subsp. pekinesis) is a vital leafy vegetable crop that thrives within the temperature range of 12 °C to 22 °C. However, high temperatures can adversely impact its growth, development, and yield. To address this issue, we investigated the potential of eugenol and clove essential oil in enhancing stress tolerance in Chinese cabbage. Transcriptome profiling of Chinese cabbage exposed to eugenol, clove essential oil, and heat stress revealed significantly differentially expressed genes (DEGs). Gene set enrichment analysis indicated that treatment with eugenol and clove essential oil significantly influenced defense responses, hormone signaling pathways, and leaf senescence. Additionally, WRKY, ERF, and NAC transcription factors were found to be enriched among the significant DEGs. Notably, eugenol and clove essential oil treatments, as well as exposure to heat stress, were associated with the regulation of leaf senescence. Furthermore, the application of eugenol and clove essential oil mitigated the heat-induced reductions in the contents of chlorophyll a, chlorophyll b, and total chlorophyll in Chinese cabbage. In summary, our findings suggest that eugenol and clove essential oil effectively enhance thermotolerance in Chinese cabbage by modulating leaf senescence and hormone responses.